HUBUNGAN LITERASI DIGITAL DENGAN HASIL BELAJAR IPS SISWA KELAS 7 SMP - Lina Septia Gevira; Aisyah Nur Sayidatun Nisa (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The evolution of 21st-century learning demands the integration of digital literacy as a key competency in supporting critical thinking skills and student learning outcomes. Digital literacy is defined as the ability to access, understand, evaluate, and utilize digital information appropriately and responsibly. This study aims to analyze the relationship between digital literacy and the social studies learning outcomes of seventh-grade students at SMP Negeri 8 Semarang on the topic of Social Interaction. This study employs a quantitative approach with a correlational design. The sample consisted of 72 students selected via simple random sampling from a population of 255 students. Learning achievement data were obtained from daily Social Studies test scores on the topic of Social Interaction, while digital literacy data were collected via a questionnaire that had been validated for both validity and reliability. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and Spearman’s rho correlation test. The results indicated that the data were not normally distributed, so a nonparametric test was used. The correlation test yielded a coefficient of 0.042 with a significance level of 0.725 (p > 0.05), indicating that there is no significant relationship between digital literacy and social studies learning outcomes. This relationship exhibits a very low degree of strength. The results suggest that digital literacy has not yet become a determining factor in the achievement of social studies learning outcomes for the material under study.